STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT AT THE ELEVENTH GRADE OF SMA NEGERI 1 TELUK DALAM - Telaumbanua, Fikah Wahyuni (Universitas Nias Raya, 2024)
This study dealt with how students' ability in writing descriptive text at the eleventh grade of SMA Negeri 1 Teluk Dalam. The purpose of this study was to describe students' ability in writing descriptive text. This research used qualitative research. The data were taken from 26 descriptive text that made by students. The data source was eleventh students at SMA Negeri 1 Teluk Dalam Academic Year 2023/2024. The researcher used documentation technique to collect the students’ writing of descriptive text. The finding shows that students’ abilities in writing descriptive text were based on five assessment components in writing. First, the content component with an average score 20.1 or including fair criteria, second, the organization component with an average score 15.8 or including good criteria, third, the vocabulary component with an average score 13.3 or including fair criteria, fourth, the language use component with an average score 15.6 or including fair criteria, and lastly, mechanics component with an average score 4.3 or including good criteria. From the result of the data, only 2 components were classified into good criteria and there are 3 components under the good criteria. This is proven based on the students’ level of difficulty in writing descriptive text. Lastly, the result of data analysis of students’ ability in writing descriptive text at the eleventh grade of SMA Negeri 1 Teluk Dalam was categorized in fair.